Reservoir releases and land cover interact to drive event-scale nitrate export in a large agricultural basin - Camden Hatley; Erin C. Seybold; Sam Zipper; Amy J. Burgin; Dustin W. Kincaid; Li Li; Julia N. Perdrial; Donna M. Rizzo; Kristen L. Underwood (Journal of Hydrology, 2026)

Lagged streamflow depletion due to pumping-induced stream drying: Incorporation into analytical streamflow depletion estimation methods - Sam Zipper; Ian Gambill; Monty Schmitt; Claire Kouba; Leland Scantlebury; Thomas Harter; Nicholas P. Murphy (Journal of Hydrology, 2026)

Variability of an adaptive capacity index to construction method and socio-economic context - Denise Chavez; Katherine Nelson; Sam Zipper (Natural Hazards, 2026)

In-silico evidence for improving irrigated maize productivity in the Great Plains: A high-resolution spatial simulation approach - Ikenna Onyekwelu; Sam Zipper; Stephen Welch; Xiaomao Lin; Vaishali Sharda (Computers and Electronics in Agriculture, 2025)

Using values-informed mental models to understand farmer, water manager, and scientist use and perceptions of hydrologic models - Nouman Afzal; Logan J. Swenson; Sam Zipper; Adam Zwickle; Chloe B. Wardropper (Journal of Hydrology, 2025)

STICr: An open-source package and workflow for stream temperature, intermittency, and conductivity (STIC) data - Sam Zipper; Christopher T. Wheeler; Delaney M. Peterson; Stephen C. Cook; Sarah E. Godsey; Ken Aho (Environmental Modelling & Software, 2025)

Current trends and biases in groundwater modelling using the community-driven groundwater model portal (GroMoPo) - Daniel Zamrsky; Sacha Ruzzante; Kyle Compare; Daniel Kretschmer; Sam Zipper; Kevin M. Befus; Robert Reinecke; Yara Pasner; Tom Gleeson; Kristen Jordan; Mark Cuthbert; Anthony M. Castronova; et al. (Hydrogeology Journal, 2025)
Groundwater, Earth’s largest nonfrozen freshwater reservoir, is vital for water supply security. Groundwater models help to manage complex domestic, agricultural, and industrial water demands while preserving ecosystem health under climate change. The community-driven groundwater model portal (GroMoPo) hosts groundwater model metadata to analyse biases and distribution of groundwater models. Over 450 models are currently featured on GroMoPo, with most models from high-GDP countries at local-to-regional scales. The GroMoPo initiative addresses current knowledge gaps and facilitates future collaboration and data sharing.

Using national hydrologic models to obtain regional climate change impacts on streamflow basins with unrepresented processes - Patience Bosompemaa; Andrea Brookfield; Sam Zipper; Mary C. Hill (Environmental Modelling & Software, 2025)

PyCHAMP: A crop-hydrological-agent modeling platform for groundwater management - Chung-Yi Lin; Maria Elena Orduna Alegria; Sameer Dhakal; Sam Zipper; Landon Marston (Environmental Modelling & Software, 2024)

Nonlinear trends in signatures characterizing non-perennial US streams - Kanak Kanti Kar; Tirthankar Roy; Sam Zipper; Sarah E Godsey (Journal of Hydrology, 2024)

Non-perennial stream networks as directed acyclic graphs: The R-package streamDAG - Ken Aho; Cathy Kriloff; Sarah E. Godsey; Rob Ramos; Chris Wheeler; Yaqi You; Sara Warix; DeWayne Derryberry; Sam Zipper; Rebecca L. Hale; Charles T. Bond; Kevin A. Kuehn (Environmental Modelling & Software, 2023)